2007
DOI: 10.1295/polymj.pj2006260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Helical Poly(macromonomer) Consisting of Polyacetylene Main Chain and Poly(methyl methacrylate) Side Chains

Abstract: ABSTRACT:The Rh-catalyzed polymerization of an acetylene-terminated poly(methyl methacrylate) (PMMA) macromonomer (M-PMMA) provided a helical poly(macromonomer), poly(M-PMMA) [M w up to 136,000, weightaverage degree of polymerization (DP w ) = 80], consisting of a polyacetylene main chain and PMMA side chains. The macromonomer M-PMMA was synthesized by ATRP of MMA initiated by a functionalized initiator, 2-bromo-2-methylpropionic acid (S)-1-methylpropargyl ester (l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Namely, the side chain is derived from metal-catalyzed system, while the main chain is done from other system. In actual, the macromonomers include functional groups, such as norbornene (MM- 18 ) and cyclobutene (MM- 19 ), applicable to ring-opening metathesis polymerization (ROMP), diene (MM- 20 ) to acyclic diene metathesis polymerization (ADMET), acetylene (MM- 21 , MM- 22 , 23 , MM- 24 , MM- 25 ) to rhodium-catalyzed polymerization, and thiophene (MM- 26 ) to electrochemical polymerization. Typically, acetylene-end-functionalized polymers (MM- 21 to MM- 25 ) are synthesized by copper-catalyzed living radical polymerization of styrene or MMA in conjunction with an alkyne-functionalized initiator such as FI- 30 (for MM- 21 ).…”
Section: Precision Polymer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the side chain is derived from metal-catalyzed system, while the main chain is done from other system. In actual, the macromonomers include functional groups, such as norbornene (MM- 18 ) and cyclobutene (MM- 19 ), applicable to ring-opening metathesis polymerization (ROMP), diene (MM- 20 ) to acyclic diene metathesis polymerization (ADMET), acetylene (MM- 21 , MM- 22 , 23 , MM- 24 , MM- 25 ) to rhodium-catalyzed polymerization, and thiophene (MM- 26 ) to electrochemical polymerization. Typically, acetylene-end-functionalized polymers (MM- 21 to MM- 25 ) are synthesized by copper-catalyzed living radical polymerization of styrene or MMA in conjunction with an alkyne-functionalized initiator such as FI- 30 (for MM- 21 ).…”
Section: Precision Polymer Synthesismentioning
confidence: 99%
“…They efficiently work as macromonomers in rhodium-catalyzed living polymerization to give well-controlled cylindrical polymer brushes consisting of a highly cis-transoidal poly(phenylacetylene) main chain and either polystyrene or poly(MMA) side chain (M w /M n ≈ 1.1). 877 Polymerization of chiralitycontaining MM-24 878 and MM-25 879 predominantly provides one-handed helical structures onto the obtained graft copolymers.…”
Section: Grafting Throughmentioning
confidence: 99%
“…The color of the reaction solutions was stable after 24 h and the reactions were stopped by purification of the products. 36 The formation of poly(ProDOT-PMMA) branched polymers was followed by size exclusion chromathography SEC-MALS. In the SEC-MALS traces (Fig.…”
Section: Homopolymerization Of Prodot-pmma Macromonomersmentioning
confidence: 99%
“…We recently reported that Rh-based poly(1-methylpropargyl alcohol)s adopt helical conformations in solution . Since the hydroxy group is easily esterified, it is possible to synthesize helical poly(1-methylpropargy ester)s substituted with functional groups exhibiting fluorescence and redox property and also helical graft copolymers (Chart ) . The presence of a chiral group in a close proximity to the main chain is quite effective at inducing a helix stabilized by steric repulsion between the side chains.…”
Section: Introductionmentioning
confidence: 99%